Relation of Dysglycemia to Structural Brain Changes in a Multiethnic Elderly Cohort. Issue 2 (5th December 2016) - Reitz, Christiane; Guzman, Vanessa A.; Narkhede, Atul; DeCarli, Charles; Brickman, Adam M.; Luchsinger, José A.
Abstract : Objectives: Abnormally high glucose levels (dysglycemia) increase with age. Epidemiological studies suggest that dysglycemia is a risk factor for cognitive impairment but the underlying pathophysiological mechanisms remain unclear. The objective of this study was to examine the relation of dysglycemia clinical categories (normal glucose tolerance (NGT), pre‐diabetes, undiagnosed diabetes, known diabetes) with brain structure in older adults. We also assessed the relation between dysglycemia and cognitive performance. Design: Cross‐sectional and longitudinal cohort study. Setting: Northern Manhattan (Washington Heights, Hamilton Heights, and Inwood). Participants: Medicare recipients 65 years and older. Measurements: Dysglycemia categories were based on HBA1c or history of type 2 diabetes (diabetes). Brain structure (brain infarcts, white matter hyperintensities (WMH) volume, total gray matter volume, total white matter volume, total hippocampus volume) was assessed with brain magnetic resonance imaging; cognitive function (memory, language and visuospatial function, speed) was assessed with a validated neuropsychological battery. Results: Dysglycemia, defined with HbA1c as a continuous variable or categorically as pre‐diabetes and diabetes, was associated with a higher number of brain infarcts, WMH volume and decreased total white matter, gray matter and hippocampus volumes cross‐sectionally, and a significant decline in gray matter volume longitudinally. Dysglycemia was also associated with lower performance in language, speed and visuospatial function although these associations were attenuated when adjusted for education, APOE‐ ε 4, ethnic group and vascular risk factors. Conclusion: Our results suggest that dysglycemia affects brain structure and cognition even in elderly survivors, evidenced by higher cerebrovascular disease, lower white and gray matter volume, and worse language and visuospatial function and cognitive speed.